1996
DOI: 10.1111/j.1550-7408.1996.tb03997.x
|View full text |Cite
|
Sign up to set email alerts
|

Primary Structure and Phylogenetic Relationships of Glyceraldehyde‐3‐Phosphate Dehydrogenase Genes of Free‐Living and Parasitic Diplomonad Flagellates

Abstract: Complete nucleotide sequences have been established for two genes (gap1 and gap2) coding for glyceraldehyde-3-phosphate dehydrogenase (GAPDH, EC 1.2.1.12) homologs in the diplomonad Giardia lamblia. In addition, almost complete sequences of the GAPDH open reading frames were obtained from PCR products for two free-living diplomonad species, Trepomonas agillis and Hexamita inflata, and a parasite of Atlantic salmon, an as yet unnamed species with morphological affinities to Spironucleus. Giardia lamblia gap1 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0
5

Year Published

1996
1996
2015
2015

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 63 publications
3
34
0
5
Order By: Relevance
“…In addition, it has been suggested that typical eukaryotic cytosolic glyceraldehyde-3-phosphate dehydrogenase genes may derive from the mitochondrial endosymbiont (26). If this is correct, then the existence of eukaryotic cytosolic glyceraldehyde-3-phosphate dehydrogenase genes in G. lamblia (26), other diplomonads (34) and Microsporidia (A.J.R., unpublished data) may also betray the secondary loss of mitochondria in these groups. However, further evidence is needed and a concentrated search for endosymbiotically-derived genes in these deeply-branching amitochondrial groups may help to decide which groups, if any, truly never had mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been suggested that typical eukaryotic cytosolic glyceraldehyde-3-phosphate dehydrogenase genes may derive from the mitochondrial endosymbiont (26). If this is correct, then the existence of eukaryotic cytosolic glyceraldehyde-3-phosphate dehydrogenase genes in G. lamblia (26), other diplomonads (34) and Microsporidia (A.J.R., unpublished data) may also betray the secondary loss of mitochondria in these groups. However, further evidence is needed and a concentrated search for endosymbiotically-derived genes in these deeply-branching amitochondrial groups may help to decide which groups, if any, truly never had mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…There is, however, some reason to believe that a number of nominally eukaryotic proteins, including those of the amitochondrial lineages, may be the descendants of diverse bacterial ancestors. We postpone a resolution of this issue until we consider other data suggesting that the nominal archaeazoans are not taxa from deeply diverging branches of the eukaryote tree (50,53,55,86,96,154,156).…”
Section: Vol 64 2000mentioning
confidence: 99%
“…The classification of H. inflata with G. lamblia is also supported by a comparison of the glyceraldehyde-3-phosphate dehydrogenase sequences of G. lamblia, Trepomonas agilis, H. inflata, and Spironucleus sp. (287). A comparison of the SS rRNA sequences of Giardia, Hexamita, Trepomonas, and Spironucleus, all diplomonads, showed that all were phylogenetically related and that the last three comprised one clade while Giardia occupied another clade (46).…”
Section: Giardia and Other Diplomonads As Early-branching Eukaryotesmentioning
confidence: 99%